The Influence of Teamwork, Internal Work Environment and Financial Compensation on Employee Performance: Pengaruh Teamwork, Lingkungan Kerja Internal dan Kompensasi Finansial Terhadap Kinerja Karyawan - Nadia Rahma Ayu Wijayanti; Dewi Andriani (Academia Open, 2021)
This study aims to determine the effect of Teamwork, Internal Work Environment and Financial Compensation on Employee Performance at Sold Out Distros in Tulangan Sidoarjo. The method used in this research is a quantitative approach method. Sampling in this study was carried out using a non-probability sampling method with a saturated sample technique with a total of 95 respondents who became employees at Sold Out Distro in Tulangan Sidoarjo. Data collection techniques using a questionnaire. The data analysis technique used in this study uses multiple linear regression using the SPSS Statistics version 22 program. The results in this study prove that Teamwork has a partial effect on Employee Performance, Internal Work Environment partially affects Employee Performance and Financial Compensation partially affects Employee performance.